Regulatory T cells produce profibrotic cytokines in the skin of patients with systemic sclerosis - MacDonald, Katherine G.; Dawson, Nicholas A.J.; Huang, Qing; Dunne, James V.; Levings, Megan K.; Broady, Raewyn (Journal of allergy and clinical immunology, 2015)
Systemic sclerosis (SSc) is an autoimmune disorder characterized by fibrosis of the skin and internal organs. Pathologic conversion of regulatory T (Treg) cells into inflammatory cytokine–producing cells is thought to be an important step in the progression of autoimmunity, but whether loss of normal Treg cell function contributes to SSc is unknown. We sought to determine whether Treg cells in the blood and skin of patients with SSc acquired abnormal production of effector cytokines. Peripheral blood and skin biopsy specimens were collected from control subjects and patients with limited or diffuse SSc. Flow cytometry was used to evaluate expression of cell-surface proteins and the cytokine production profile of forkhead box protein 3–positive Treg cells compared with forkhead box protein 3–negative conventional T cells. Treg cells in the blood of patients with SSc had a normal phenotype and did not produce T-effector cytokines. In contrast, Treg cells from skin affected by SSc produced significant amounts of IL-4 and IL-13. Although Treg cells in the blood of patients with SSc did not make TH2 cytokines, they contained a significantly higher proportion of skin-homing cells expressing TH2 cell–associated chemokine receptors. Evidence that IL-33 caused the differentiation of skin Treg cells into TH2-like cells, combined with high tissue-localized expression of this cytokine in patients with SSc and expression of the ST2 chain of the IL-33 receptor on skin-localized Treg cells, suggests that IL-33 might be an important stimulator of tissue-localized loss of normal Treg cell function. These data are the first evidence for the presence of TH2-like Treg cells in human autoimmunity and show that Treg cell plasticity can be tissue specific. Localized dysfunction of Treg cells is a previously unknown factor that might contribute to fibrosis in patients with SSc.